A survey to investigate the association of pain, foot disability and quality of life with corns. Issue 1 (December 2015) - Farndon, Lisa; Concannon, Michael; Stephenson, John
Abstract Background Corns are a common foot problem affecting a large proportion of the population. This study describes the characteristics of corns experienced by 201 participants taking part in a randomised controlled trial to investigate associations between demographic and corn parameters on pain, foot related disability and quality of life (QoL). Methods Pain from the main (index) corn was measured using a visual analogue scale (VAS); foot related disability was assessed with the Foot Disability Questionnaire (now known as the Manchester Foot Pain and Disability Index) and quality of life was recorded with the EQ-5D questionnaire. The effect of demographic and corn parameters on the pain and quality of life outcomes was assessed with analysis of variance (ANOVA) methods. The effect of the same factors on a linear combination of the foot-related disability outcome measures was assessed using multivariate ANOVA methods. Pain was also tested for its mediating properties on the causal pathway between the independent variables and quality of life. Results The mean pain score was 5.29 points on a 10 cm VAS, with females reporting substantively higher pain levels than males. Age affected foot-related disability, with lower levels on all domains of the MFPDI reported in older participants; each year of advancing age was associated with falls of: 0.009 points on the Concern about Appearance (CA) domain; 0.047 points on the Functional Limitation (FL) domain and 0.048 points on the Pain Intensity (PI) domain. Sex and corn type also affected disability, with higher scores reported by females and participants with plantar corns. Conclusions The effect of pain was shown to mediate the relationship between sex and foot-related disability. The presence of plantar corns has a more detrimental effect on QoL than dorsal/inter-digital corns. Trial registration ISRCTN 13166839